2019
DOI: 10.1186/s42506-019-0014-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, determinants, and outcomes of unintended pregnancy in Sohag district, Egypt

Abstract: Background: Unintended pregnancies may be mistimed or unwanted. It represents 40% of all pregnancies, and it had multiple risky health outcomes. It is essential to understand the factors affecting unintended pregnancies and their consequences to develop strategies that help prevent them. The present study is conducted to identify the prevalence, determinants, and outcomes of unintended pregnancies in Sohag district, Egypt. Methods: A cross-sectional study was conducted in Sohag district, 2016. Five hundred fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 15 publications
8
32
1
3
Order By: Relevance
“…Women in rural areas are more likely to experience unwanted pregnancies than in urban areas. This study shows the same results with research conducted in Egypt [7]. These results do not agree with other studies conducted in Sudan [8] which reported no significant differences between urban and rural women.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Women in rural areas are more likely to experience unwanted pregnancies than in urban areas. This study shows the same results with research conducted in Egypt [7]. These results do not agree with other studies conducted in Sudan [8] which reported no significant differences between urban and rural women.…”
Section: Resultscontrasting
confidence: 59%
“…Unwanted pregnancy is an important public health problem throughout the world. It not only affects women, but also affects their families and communities [7]. Table 1 shows that unwanted pregnancy among respondents in urban areas is greater [8.9%] than in rural areas [6.3%].…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that cultural factors strongly affect the parent-child relationship, which subsequently is related to reproductive behaviors [4]. However, human behaviors, including fertility behavior, are dependent on the social and cultural factors and individual and cultural differences that exist in communities and lead to different fertility behaviors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Kenya, Egypt, Nigeria and South Africa indicated that the prevalence of unintended pregnancies was 24%, 30.7%, 35.9% and 64.33% respectively (8)(9)(10)(11). According to studies conducted in different parts of Ethiopia, the prevalence of unintended pregnancy ranged from 13.7%to 41.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different African countries identified that age, place of residence, marital status, ethnicity, types of employment, educational status, numbers of living children, monthly income and women autonomy, parity, gravidity, knowledge on contraceptives, accessibility of contraceptives as determinants of unintended pregnancy (8)(9)(10)(11)20). Similarly, studies conducted in various parts of Ethiopia identified age, residence, religion, marital status, parity, visiting health professionals, history of abortion, age at first birth, family size, educational status, gravidity, distance from health facility, history of still birth and knowledge on modern contraceptive methods as determinants of unintended pregnancy (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%